Salinity-tolerant larvae of mosquito vectors in the tropical coast of Jaffna, Sri Lanka and the effect of salinity on the toxicity of Bacillus thuringiensis to Aedes aegypti larvae - Jude, P.J.; Tharmasegaram, T.; Sivasubramaniyam, G.; Senthilnanthanan, M.; Kannathasan, S.; Raveendran, S.; Ramasamy, R.; Surendran, S.N. (My University, 2012)
Dengue, chikungunya, malaria, filariasis and Japanese encephalitis are common mosquito-borne diseases endemic to Sri Lanka. Aedes aegypti and Aedes albopictus, the major vectors of dengue, were recently shown to undergo pre-imaginal development in brackish water bodies in the island. A limited survey of selected coastal localities of the Jaffna district in northern Sri Lanka was carried out to identify mosquito species undergoing pre-imaginal development in brackish and saline waters. The effect of salinity on the toxicity of Bacillus thuringiensis israelensis larvicide to Ae. aegypti larvae at salinity levels naturally tolerated by Ae. aegypti was examined. Larvae collected at the selected sites along the Jaffna coast were identified and salinity of habitat water determined in the laboratory. The LC50 and LC90 of B. thuringiensis toxin, the active ingredient of a commercial formulation of the larvicide BACTIVECr, were determined with Ae. aegypti larvae. Bioassays were also carried out at salinities varying from 0 to18 ppt todetermine the toxicity of Bacillus thuringiensis to fresh and brackish water-derived larvae of Ae. aegypti. Larvae of four Anopheles, two Aedes, one Culex and one Lutzia species were collected from brackish and saline sites with salinity in the range 2 to 68 ppt. The LC50 and LC90 of B. thuringiensis toxin for the second instar larvae of Ae. aegypti in fresh water were 0.006 ppm and 0.013 ppm respectively, with corresponding values for brackish water populations of 0.008 and 0.012 ppm respectively. One hundred percent survival of second instar fresh water and brackish water-derived Ae. aegypti larvae was recorded at salinity up to 10 and 12 ppt and 100% mortality at 16 and 18 ppt, yielding an LC 50 for salinity of 13.9 ppt and 15.4 ppt at 24 h post-treatment respectively for the two populations. Statistical analysis showed significantly reduced toxicity of B. thuringiensis to fresh and brackish water-derived
Keywords: Aedes aegypti; Bacillus thuringiensis; Dengue; Jaffna; Mosquito vectors; Salinity; Sri Lanka